Paweł Hertz’s Italy - Płaszczewska, Olga (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article is an attempt at reconstructing the remarks by Paweł Hertz (essayist, poet, translator, writer and publisher) on Italy and its artistic legacy. A short presentation of the writer is followed by a discussion of his actual journeys in Italy based on the available autobiographical material. Next,there are reflections on Hertz’s interest in Italian literature and European texts about Italy (based on essays and editorial work). Treated as a separate issue is the view of Italian art through the prism of Polish artistic work (the spheres of associations, interference and references) in Hertz’s journalism. Other issues discussed in the article cover poems about Italy, their place among the writer’s works and the main threads and motifs. The article’s final notes focus on the observations on the value of Polish reception of Italian cultural legacy and its basic aspects that Hertz regularly emphasised at various stages of his creative life.